Evaluation of best price clauses in online hotel booking - Matthias Hunold; Reinhold Kesler; Ulrich Laitenberger; Frank Schlütter (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
We analyze the best price clauses (BPCs) of online travel agents (OTAs) using meta-search price data of nearly 30,000 hotels in different countries. We find that BPCs influence the pricing and availability of hotel rooms across online sales channels. In particular, hotels publish their offers more often at Booking.com when it does not use the narrow BPC, and also tend to promote the direct online channel more actively. Moreover, the abolition of Booking.com's narrow BPC is associated with the direct channel of chain hotels having the strictly lowest price more often.
Keywords: D40; L42; L81; 330; best price clauses; hotel booking; MFN; OTA; vertical restraints